The Effect Of Internal And External Company Factors On Stock Underpricing - Fadli, Muhammad Mutohar; Purwanti, Lilik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study seeks to investigate and analyze the effect of both internal and external company factors on stock underpricing. The internal factors considered include current ratio, return on assets, and firm size, while the external factors encompass underwriter reputation, the rupiah exchange rate, and market sentiment. The research population consists of 179 companies that launched IPOs on the Indonesia Stock Exchange (IDX) between 2022 and 2024, from which 68 samples of established criteria are selected through a purposive sampling, and analyzed by multiple linear regression. The findings suggest that internal factors such as current ratio, firm size, and market sentiment negatively affect stock underpricing, whereas return on assets has a positive effect. Additionally, the results indicate that the external factors, including underwriter reputation do not exert a negative effect, and the rupiah exchange rate does not have a positive effect on underpricing. This study recommends that investors, IPO companies, and underwriters consider the current ratio, return on assets, firm size, and market sentiment when assessing the effect of underpricing.